Effect of heat treatment on grain boundary carbides and primary water stress corrosion cracking resistance of Alloy 182 weld. (October 2021) - Kim, Ho-Sub; Chen, Junjie; Lee, Hyeon Bae; Shin, Ji Ho; Kong, Byeong Seo; Oh, Seungjin; Jang, Hun; Jang, Changheui
Highlights: PWSCC resistance of Alloy 182 weld was improved after heat-treatment at 620 and 650 °C. GB carbides were Cr23 C6 for as-welded specimen, but M7 C3 type after heat treatment. Depth of oxidized GB ahead of crack decreased due to less Cr supply from Cr7 C3 carbides. Improvement in PWSCC resistance was, in part, caused by the formation of Cr7 C3 carbides. Abstract: Alloy 182 welds were heat-treated at 600, 620, and 650 °C for 10 h. The primary water stress corrosion cracking initiation test showed significant improvement in the cracking resistance of the heat-treated specimens over the as-welded specimens. Microstructure analysis demonstrated that Cr23 C6 grain boundary carbides dominated in the as-welded specimen, while Cr7 C3 carbides were dominant after heat treatment. The depth of grain boundary oxidation ahead of the crack tip was large for the as-welded specimen, but less for the heat-treated specimens. Therefore, the presence of Cr7 C3 carbides, in part, contributed to the improved cracking resistance of the Alloy 182 weld.